E-learning on medical emergencies for Dentistry students: a randomized controlled trial - Teixeira, Jéssica Vargas (2021)
This study compared two teaching pedagogies to address medical emergencies in dental office visits and evaluated dental school students' knowledge about medical emergencies. This randomized controlled trial involved 54 senior undergraduate dental students at the Federal University of Santa Maria divided in two groups: students who received instruction via face-to-face traditional expository class; and students who received the same instruction via distant learning format. The students were randomly allocated to the groups by the randomiser.org website. Data were obtained by comparing the scores students received from answering to a semi-structured questionnaire containing inquiries on ethical and legal implications, and diagnosis and management of medical emergencies in a dental office before and after the instruction. Before the instruction, 96% of students from the two groups lacked knowledge about the ethical and legal implications related to the dentist obligation to deal with medical emergencies. After the instruction, both groups increased their knowledge similarly as there was no significant difference in the comparison between learning about medical emergencies through lectures and thorough an e-learning format. Both teaching methods presented satisfactory results, which makes the e-learning method an option as a didactic strategy.